Health Behavior, Health Service Use, and Health Related Quality of Life of Adult Women in One-person and Multi-person Households - Hyun Ju Chae; MiJong Kim (Korean Society of Women Health Nursing, 2019)
PURPOSE: This study was to identify health behavior, health service use, and health related quality of life of adult women in one-person and multi-person households. METHODS: It was used data from the 7th Korea National Health and Nutrition Examination Survey (KNHANES VII-2017). Subjects were 2,522 women with age of 19 to 64 years in 2017. Complex sampling design and data analysis were performed using SPSS 20.1. RESULTS: Women in one-person households had higher rates of alcohol drinking (χ²=13.77, p=.003), smoking (χ²=16.07, p=.001), unmet medical care (χ²=8.77, p=.004) and non-practice of cancer screening (χ²=13.77, p=.003) compared to women in multi-person households. Health-related quality of life was also lower for women in one-person households (t=−2.46, p=.015). Factors affecting health-related quality of life in one-person households were household income, job status, and unmet dental care, having 32.4% explanatory power. One-person household women with low incomes, no jobs, and unmet dental care showed low health-related quality of life. In comparison, factors affecting health-related quality of life of women in multi-person household women were age, education level, unmet medical care, and unmet dental care, having 10.4% explaining power. Women in multi-person households with age of 60-64, low education level, unmet medical care, and unmet dental care showed low health-related quality of life. CONCLUSION: Health promotion strategies should be developed based on unique understanding of social, economic, and health of adult women in one-person and multi-person households.